Effect of Blast Loading on Seismically Detailed RC Columns and Buildings - Marco Fouad; Mohamed N. Fayed; Gehan A. Hamdy; Amr Abdelrahman (Civil Engineering Journal, 2021)
Explosions caused by standoff charges near buildings have drastic effects on the internal and external structural elements which can cause loss of life and fatal injuries in case of failure or collapse of the structural element. Providing structural elements with blast resistance is therefore gaining increasing importance. This paper presents numerical investigation of RC columns with different reinforcement detailing subjected to near-field explosions. Detailed finite element models are made using LS-DYNA software package for several columns having seismic and conventional reinforcement detailing which were previously tested under blast loads. The numerical results show agreement with the published experimental results regarding displacements and damage pattern. Seismic detailing of columns enhances the failure shape of the column and decrease the displacement values compared to columns with conventional reinforcement detailing. Further, the effect of several modeling parameters are studied such as mesh sensitivity analysis, inclusion of air medium and erosion values on the displacements and damage pattern. The results show that decreasing the mesh size, increasing erosion value and inclusion of air region provide results that are very close to experimental results. Additionally, application is made on a slab-column multistory building provided with protective walls having different connection details subjected to blast loads. The results of this study are presented and discussed. Use of a top and bottom floor slab connection of protective RC walls are better than using the full connection at the four sides to the adjacent columns and slabs. This leads to minimizing the distortion and failure of column, and therefore it increases the chance of saving the building from collapse and saving human lives. Doi: 10.28991/cej-2021-03091733 Full Text: PDF